2002
DOI: 10.5597/lajam00023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the conservation status of a franciscana (<i>Pontoporia blainvillei</i>) stock in the Franciscana Management Area III following the IUCN Red List Process

Abstract: The IUCN Red List of Threatened Species is the most widely followed and comprehensive inventory of the conservation status of species. Recently, the Red List programme changed in several ways including, revisions to the criteria for determining species statuses and the development of a process for challenging statuses. In the 2000 Red List, the franciscana (Pontoporia blainvillei) was listed as Data Deficient, which indicates that data were insufficient to determine the status of the species under the Red List… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…In addition, bycatch is known to threaten several other populations (e.g. franciscana Pontoporia blain villei, Secchi & Wang 2002; Hector's dolphin Ce phalorhynchus hectori, Slooten et al 2000; Baltic harbour porpoises Phocoena phocoena, Berggren et al 2002). Considering that small cetaceans use sound both for communication and echolocation, it is not surprising that acoustic devices have been explored as a tool for reducing bycatch.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bycatch is known to threaten several other populations (e.g. franciscana Pontoporia blain villei, Secchi & Wang 2002; Hector's dolphin Ce phalorhynchus hectori, Slooten et al 2000; Baltic harbour porpoises Phocoena phocoena, Berggren et al 2002). Considering that small cetaceans use sound both for communication and echolocation, it is not surprising that acoustic devices have been explored as a tool for reducing bycatch.…”
Section: Introductionmentioning
confidence: 99%
“…Ott et al, 2002;Secchi and Wang, 2002;Secchi et al, 2003b), and was first observed about sixty years ago in shark gillnet fisheries off Uruguay (Van Erp, 1969). Although gillneting in southern Brazil and Argentina emerged in the 1940s (Haimovici et al, 1997;E.…”
Section: Introductionmentioning
confidence: 99%
“…Although the largest documented catches in the 1970s were in Uruguay, catches in recent decades have also been high in southern Brazil and Argentina (Praderi et al 1989;Pérez Macri and Crespo 1989;Monzón and Corcuera 1991;Secchi et al 1997;Secchi 1999). Available evidence suggests that mortality rates are excessive and unsustainable (Crespo 1998;Secchi and Wang 2002). Scientists in the three range countries are well aware of the need for more research and conservation action, but they need external support.…”
Section: Franciscana (La Plata Dolphin) Pontoporia Blainvilleimentioning
confidence: 99%